Modeling the relationship between cortisol, dopaminergic and serotonergic metabolic pathways in the etiology of depressive behavior - Dalvi-Garcia, Felipe (2019)
Symptoms of Major Depressive Disorder (MDD) include depressive mood, anhedonia, reduced energy, sleep problems, reduced or increased appetite, bouts of anxiety, and others. The monoamine imbalance hypothesis is currently the most widely accepted neurobiological theory regarding the etiology of MDD. Additionally, persistently high levels of circulating stress hormones, which decrease the levels of monoamines like serotonin and dopamine, have been described as triggers of MDD. Specifically, impaired neurotransmission plays a key role in the prefrontal cortex (PFC) and can culminate in the onset of MDD. In this work, an integrated computational model was developed to investigate the dynamics between dopaminergic, serotonergic-kynurenine metabolisms and cortisolemia, and the consequences of such interactions on the onset of depressive behavior. This deterministic model was developed using a set of nonlinear ordinary differential equations represented with power-law functions. Parameter values were obtained from de novo experimental data and from data reported in biological databases and fine-tuned per optimization. The model was validated with additional literature data that had not been used for model construction. Sensitivity analysis demonstrates that the mathematical structure of the model is quantitatively consistent with the behavior of the biological system exposed to small perturbations. The model is also semi-quantitatively consistent with other experimental and clinical data. In particular, model simulations showed that higher levels of glucocorticoids lead to increased levels of aldehydes derived from dopaminergic and serotonergic metabolism and to augmented neurotoxic risk, due to imbalances in the kynurenine pathway during cortisolemia. The results point out the deleterious underlying effects in the monoamine pathways due to increased kynurenine metabolites and support the “oxido-neuroinflammation theory” for the etiology of depressive- like behavior due to chronic psychological stress.